Assessment of Total Hip Arthroplasty by Means of Computed Tomography 3D Models and Fracture Risk Evaluation. Issue 6 (2nd April 2013) - Gargiulo, Paolo; Pétursson, Throstur; Magnússon, Benedikt; Bifulco, Paolo; Cesarelli, Mario; Izzo, Gianluca Mario; Magnúsdóttir, Gígja; Halldórsson, Grétar; Ludvigsdóttir, Gudbjörg K.; Tribel, Jan; Jónsson, Halldor
Abstract Total hip arthroplasty (THA) can be achieved by using a cemented or noncemented prosthesis. Besides patient's age, weight, and other clinical signs, the evaluation of the quality of the bones is a crucial parameter on which orthopedic surgeons base the choice between cemented and noncemented THA. Although bone density generally decreases with age and a cemented THA is preferred for older subjects, the bone quality of a particular patient should be quantitatively evaluated. This study proposes a new method to quantitatively measure bone density and fracture risk by using 3D models extracted by a preoperative computed tomography (CT) scan of the patient. Also, the anatomical structure and compactness of the quadriceps muscle is computed to provide a more complete view. A spatial reconstruction of the tissues is obtained by means of CT image processing, then a detailed 3D model of bone mineral density of the femur is provided by including quantitative CT density information (CT must be precalibrated). A finite element analysis will provide a map of the strains around the proximal femur socket when solicited by typical stresses caused by an implant. The risk for structural failure due to press‐fitting and compressive stress during noncemented THA surgery was estimated by calculating a bone fracture risk index (ratio between actual compressive stress and estimated failure stress of the bone). A clinical trial was carried out including 36 volunteer patients (ages 22–77) who underwent unilateral THA surgery for the first time: 18 received a cemented implant and 18 received a noncemented implant. CT scans were acquired before surgery, immediately after, and after 12 months. Bone and quadriceps density results were higher in the healthy leg in about 80% of the cases. Bone and quadriceps density generally decrease with age but mineral density may vary significantly between patients. Preliminary results indicate the highest fracture risk at the calcar and the lowest at the intertrocanteric line, with some difference between patients. An analysis of the results suggest that this methodology can be a valid noninvasive decision support tool for THA planning; however, further analyses are needed to tune the technique and to allow clinical applications. Combination with gait analysis data is planned.